Pendugaan Awal Patahan di Pulau Jawa Menggunakan Anomali Gravitasi dan Riwayat Kegempaan - Ryanto, Theo Alvin; Suntoko, Hadi; Setiaji, Abimanyu Bondan Wicaksono (EKSPLORIUM, 2019)
Information related to the fault existences is needed for industrial development planning, mainly on the Nuclear Power Plant (NPP) site planning. This study is aimed to build preliminary prediction on faults existence in Java Island by using free-air gravity and earthquakes history data. The methodologies are separating regional with residual gravity anomalies and then analyzing them by correlating the continuity of their contrast values which have similarities with the distribution of earthquakes epicenters point. Based on the analysis, some lineaments in Java Island are predicted as faults which relatively directing to north-south and west-east.